Emergency department management of older people living with frailty: a guide for emergency practitioners. Issue 9 (21st April 2021) - Hogervorst, Vera M; Buurman, Bianca M; De Jonghe, Annemarieke; van Oppen, James David; Nickel, Christian Hans; Lucke, Jacinta; Blomaard, Laura C; Thaur, Arjun; Mooijaart, Simon P; Banerjee, Jay; Wallace, James; de Groot, Bas; et al.
Abstract : Emergency Departments (EDs) are increasingly seeing more seriously unwell older people living with frailty. In the context of limited resources and increasing demand it's the ED practitioner's challenge to unpick this constellation of physical, psychological, functional and social issues.To properly assess older people living with frailty at the ED it is crucial to use an holistic approach. This consists of triage with algorithms sensitive to the higher risk of older people living with frailty, a frailty assessment, and an assessment with the help of the principles of Comprehensive Geriatric Assessment. Multi-disciplinary care, a tailor-made treatment plan, based on what the person values most, will help the ED practitioner to deliver appropriate and valuable care during the ED stay, but also in transition from hospital to home.